The Four Stragglers - Packard, Frank L. (Frank Lucius), 1877-1942 (Salt Lake City, UT : Project Gutenberg, 2019)
"The Four Stragglers" by Frank L. Packard is a fiction novel written in the early 20th century. The story begins with a chaotic scene from a battlefield, where four men, who are strangers to each other, find themselves in a thicket amid the confusion of war. As they grapple with their circumstances, the characters share their stories and backgrounds, setting the stage for a complex narrative that involves themes of survival, identity, and the impacts of conflict on individuals. At the start of the novel, the atmosphere is tense and dire, reflecting the madness of war and the confusion faced by the characters. The four men, a mix of different nationalities and military backgrounds, engage in dialogue that reveals their state of mind and their experiences$1 (Btheir camaraderie is forged in adversity. One of them, a Frenchman, converses with a British soldier, underscoring the shared desperation of those caught in the conflict. The opening prologue effectively introduces the main players and hints at the larger story that will unfold, focusing on themes of fate, survival, and the unseen connections between lives altered by war. (This is an automatically generated summary.)s
Release date is 2019-07-10
Produced by Al Haines
Keywords: Detective and mystery stories; World War, 1914-1918 -- Veterans -- Fiction